Answer:
look below
Step-by-step explanation:
y = 2 (x + 3)^2 - 2
Geometric figure: parabola
Alternate forms:
y = 2 (x + 2) (x + 4)
y = 2 (x^2 + 6 x + 8)
-2 x^2 - 12 x + y - 16 = 0
Expanded form:
y = 2 x^2 + 12 x + 16
Roots:
x = -4
x = -2
<u>Properties as a real function:
</u>
Domain
- R (all real numbers)
Range
- {y element R : y>=-2}
Partial derivatives:
d/dx(2 (x + 3)^2 - 2) = 4 (x + 3)
d/dy(2 (x + 3)^2 - 2) = 0
Implicit derivatives:
(dx(y))/(dy) = 1/(12 + 4 x)
(dy(x))/(dx) = 4 (3 + x)
Global minimum:
min{2 (x + 3)^2 - 2} = -2 at x = -3
If one is positive we can conclude that the other is also positive
Positive*positive=positive(24)
The product of the two numbers is 24
And the smaller number is less than the greater number by 2
Factors of 24=1*24,2*12,3*8,4*6.
The only pair with the diffrence of two is 4*6
Therefore the two integers are 4 and 6
First to find what’s 2x you do 25-11=14, and you know that 7 x 2 =14.
So x= 7.